Karakteristik Pangan Fungsional Nuget dan Stik dari Tepung Ikan Layang Ekor Merah (Decapterus kuroides) dan Ampas Tahu : Characteristics of Functional Food of Nugget and Stick Based on Redtail Scad (Decapterus kurroides) Flour and Tofu Dregs - Marni Kaimudin; Sumarsana Sumarsana; Mozes Sukur Yodida Radiena; Sugeng Hadi Noto (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
The potential resources of redtail scad (Decapterus kuroides) and tofu dregs which are abundant and have not been utilized optimally are assets for the people’s economy by making alternative flour as a substituent for functional processed food made from wheat flour such as nuggets and sticks. An external effort that is useful for functional food processing, a study was carried out aimed at knowing the characteristics of nuggets and sticks made from red tail scad flour and tofu dregs. The research method used is descriptive qualitative. The research treatment was the ratio between fish meal, tofu pulp flour and wheat flour with a ratio of 1:1:1, 1:2:3, 1:3:2, 2:1:3 2:3:1, 3:1:2 , 3:2:1. Nuggets product test parameters include sensory (aroma, taste, texture), water content, ash, fat, protein, lead, coliform, E.coli, Salmonella, Staphylococcus aureus and stick products include sensory (smell, color, taste, appearance), moisture content, ash, fat, protein, calcium, lead, mold. The results showed that the 3:1:2 ratio of ingredients produced nuggets and sticks with the best characteristics. Characteristics of nuggets with a sensory value of 5.96 flavor, 6.13 taste and 5.96 texture, as well as 41.59% moisture, 2.32% ash, 21.67% protein, 14.08% fat, lead <0.073 mg/kg, coliform <3 MPN/g, E.coli <3 MPN/g, Salmonella negative/25g, Staphylococcus aureus negative. Characteristics of the stick with a sensory score value of 4.70 smell, 4.57 texture, 4.52 flavour and 4.57 appearance, 22.87% moisture, 5.22% ash, 15.11% protein, 17.36% fat, 25.7 mg/kg calcium, lead <0.073 mg/kg, mold 5 colony/g. The characteristics of nugget and stick are in accordance with SNI 01-6682-2000, SNI 7587:2013 and BPOM Regulation No.16 of 2016.